EAGLE SYNDROME: REPORT OF A CASE AND A REVIEW OF LITERATURE - (:unkn) unknown (My University, 2018)
Eagle’s syndrome is defined as the symptomaticelongation of the styloid process or mineralization ofthe styloid ligament complex. It can be presented as avariety of different symptoms which can mislead theotolaryngologist and the dentist in diagnosing thiscondition. The objective of this report is to present acase report of Eagle Syndrome in a female patient andreview of literature.

Eagle sendromu stiloid proçesin semptomatik olarak uzaması veya stilohyoid ya da stilomandibular ligamanın mineralizasyonu ile karakterize bir sendrom olarak ifade edilmektedir. Bu sendrom kulak burun boğaz uzmanı ve diş hekimlerini tanı bakımından yanıltabilecek farklı belirtilerle ortaya çıkabilir. Bu makalede Eagle sendromlu bir kadın olgu literatür bilgileri doğrultusunda sunulmuştur.
EAGLE SENDROMU: OLGU SUNUMU VE LİTERATÜR DERLEMESI
Keywords: Diş Hekimliği